2017
DOI: 10.1021/acs.accounts.7b00147
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Covalent Chemistry of Carbon Dioxide: Opportunities to Address Environmental Issues

Abstract: Extraction and purification of basic chemicals from complex mixtures has been a persistent issue throughout the development of the chemical sciences. The chemical industry and academic research have grown over the centuries by following a deconstruction-reconstruction approach, reminiscent of the metabolism process. Chemists have designed and optimized extraction, purification, and transformation processes of molecules from natural deposits (fossil fuels, biomass, ores), in order to reassemble them into comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Yttrium was selected as representative of the series providing the optimal resolution for in situ qNMR, while ex situ analyses were conducted with lanthanum and yttrium (vide supra). In agreement with our previous report, 20 the rare earth elements proved to induce identical partitioning effects on the various building blocks used. In the presence of 1/12 eq.…”
Section: A(co 2 )supporting
confidence: 93%
See 2 more Smart Citations
“…Yttrium was selected as representative of the series providing the optimal resolution for in situ qNMR, while ex situ analyses were conducted with lanthanum and yttrium (vide supra). In agreement with our previous report, 20 the rare earth elements proved to induce identical partitioning effects on the various building blocks used. In the presence of 1/12 eq.…”
Section: A(co 2 )supporting
confidence: 93%
“…We and others have indeed previously shown that organic or inorganic species reversibly binding amines or carbamates, can respectively act as carbamation antagonist or agonist, favoring either capture from dilute emissions 18,19 or stripping at low enthalpic costs. 20,21 -C-N bond exchange can in principle occur at fixed CO2 loading through intra-and/or intermolecular substitution reactions (transcarbamation; scheme 1, Eq. 2 and Eq.…”
Section: A(co 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Our idea stemmed from the largely documented evidence that carbon dioxide and amines easily form carbamato adducts. 24 Thus, the present work describes a novel and simple CO2-fixation strategy to synthesize 5-aryl-2oxazolidinones bypassing the inertness of the aziridine/carbon dioxide system: exceptional simplicity and increased sustainable value with respect to existing procedures are guaranteed by operating at ambient conditions (ambient temperature, atmospheric CO2 pressure) and the complete absence of any catalyst/co-catalyst. Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…Under reduced pressure or mild heat, dissociation of CO2 from the diamines occurs, and the parent diamines can be regenerated. This reversible carbon dioxide capture process has been applied in carbon capture processes 22 , switchable solvents 16 , and heavy metal extraction 17,23 . CO2-responsive autonomous aggregation (or precipitation) was controlled by polarity alteration of the monomeric entity, which is key to induce this dynamic behaviour 24 .…”
mentioning
confidence: 99%